Agricultural Land Protection Design through Istibdal Waqf Strategy - Ridho Wahyu Dewanto; Dewi Laela Hilyatin (Universitas Muhammadiyah Sidoarjo, 2021)
This research is based on the main issue, namely the phenomenon that is happening in Sidoarjo Regency, namely the reduction of Sustainable Food Agricultural Land (LP2B). The main factor that causes this phenomenon to occur is that it is triggered by the increasing population in Sidoarjo Regency. This high population growth has resulted in a high demand for housing development. So that sustainable food agriculture land is one of the targets for housing developers to convert it into a residence without considering the balance of the surrounding environment. As a result, many farmers have lost their livelihoods and the environmental balance has been disturbed. So that we need innovative solutions to overcome the phenomenon of the reduction of sustainable food agricultural land. For this reason, the researchers designed a strategy regarding the development of land waqf through the waqf istibdal method to protect sustainable food agricultural land which is threatened with conversion of agricultural land. The istibdal method is the exchange of similar ornon-similar waqf assets. With this method, land waqf can be mutated for agricultural land. This strategy is expected to reduce land conversion and function to conserve land waqf that was not previously functional.